Pengaruh Kompetensi dan Beban Kerja Terhadap Kinerja Auditor: (Studi Empiris pada Kantor Akuntan Publik di Bali) - Annas Rahmat Ramadhani (Indonesian Accounting Literacy Journal, 2026)
The performance of auditors plays a critical role in ensuring the accuracy of financial statements and maintaining public trust in corporate internal control systems. Two key factors widely believed to influence auditor performance are competence and workload. Competence encompasses auditors’ understanding of accounting principles, technical skills, and sufficient professional experience, while workload refers to the volume and complexity of tasks that must be completed within a specified period. This study aims to examine the extent to which competence and workload affect auditor performance at Public Accounting Firms (KAP) in Bali, a region that is frequently used as a research setting for similar studies. Beyond technical aspects, this study also considers the psychological pressure experienced by auditors and public perceptions of the auditing profession. This study employs quantitative data obtained through questionnaires to measure competence, workload, and auditor performance. Primary data were collected through questionnaires, while secondary data were obtained from official documents and relevant literature. The research population consisted of 70 auditors working at KAPs in Bali, all of whom were included as a saturated sample. Data were collected through documentation and questionnaires. Data analysis involved descriptive statistics, validity and reliability testing, multiple linear regression to examine the effect of competence and workload on auditor performance, as well as classical assumption testing. Model fit testing and the coefficient of determination were also employed to evaluate model adequacy. The regression analysis results indicate that competence and workload do not have a significant effect on auditor performance, either partially or simultaneously.